Examination of air density fluctuations with the aid of laser beam - Klemm, Katarzyna; Pieszyński, Krzysztof; Różniakowski, Kazimierz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
The paper presents theoretical foundations and results of experimental verification of the possibility of laser beam application for registration of air density fluctuations caused either by mechanically forced air flow near obstacles which are not streamlined or by the presence of solid objects which produce thermal disturbance (temperature gradients).
Optica Applicata, Vol. 37, 2007, nr 3, s. 219-228
Keywords: optyka; turbulence; density fluctuations; laser application